A mitochondria-related signature for predicting immune microenvironment and therapeutic response in osteosarcoma - Zhang, Lina; Wu, Song; Huang, Junjie; Shi, Yanbin; Yin, Yuesong; Cao, Xu (Frontiers in Oncology, 2022)
Osteosarcoma remains to be the most devastating malignant tumor in children and teenagers. Mitochondria have also been proven to play critical roles in osteosarcoma. However, a mitochondria-related signature has been established in osteosarcoma for comprehensive evaluation of the pathogenic roles and regulatory roles of mitochondria in osteosarcoma. In this study, transcriptome data and clinical information of osteosarcoma samples were collected from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) and Gene Expression Omnibus (GEO) databases. A mitochondria-related signature was constructed in osteosarcoma patients. The prognostic value of the mitochondria-related signature was explored. The predictive value of the mitochondria-related signature in the immune microenvironment and chemotherapy agents was explored. The association between mitochondria and immunity in the tumor microenvironment of osteosarcoma at the single-cell RNA sequencing (scRNA-seq) level was explored. The tumorigenic role of the key mitochondria-related gene, PCCB, was verified by in vitro validation. In conclusion, a mitochondria-related signature was developed in osteosarcoma with strong predictive values in the immune microenvironment, chemotherapy agents, and prognosis.